2007
DOI: 10.1177/039463200702000322
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Gel of Carotid Artery Plaque

Abstract: Atherosclerosis is a complex disease that affects medium and large arteries, leading to the formation and progression of plaque. In this process the proteins play an essential role and as a consequence, proteomic-based strategies examining the protein content of cells or tissues could offer a useful approach for the study of plaque proteins. Due to the heterogeneous cell composition of plaque, proteome analysis of whole lesions is difficult, besides being also complicated by the presence of plasma proteins tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This type of gel is obtained by averaging the positions, shapes and optical densities of the spots in a given set of gels [43,44]. Fig.…”
Section: A Basal Level Of Protein Carbonylationmentioning
confidence: 99%
“…This type of gel is obtained by averaging the positions, shapes and optical densities of the spots in a given set of gels [43,44]. Fig.…”
Section: A Basal Level Of Protein Carbonylationmentioning
confidence: 99%
“…In this report, authors identified cathepsin D as a potential target for therapeutical treatment of atherosclerosis. Terzuoli et al, 2007;Porcelli et al, 2010) IMAC, immobilized metal affinity chromatography. ↑, increase.…”
Section: Studies On Human Tissuesmentioning
confidence: 99%
“…In this way, they identified 19 proteins with differential distribution between ICA and CCA segments. To overcome the problem of plaque heterogeneity, Terzuoli et al proposed a method for selecting proteins exclusive to plaque by constructing a reference synthetic gel (Terzuoli et al, 2007;Porcelli et al, 2010). This gel, obtained by averaging the positions, shapes and optical densities of spots in 2DE maps from 10 carotid plaque samples was compared with an equivalent synthetic gel constructed using 10 plasma samples from the same carotid surgery patients.…”
Section: Studies On Human Tissuesmentioning
confidence: 99%